The Protection of Secured Creditors in the Execution of Collateral in Bankruptcy - Ayu Puspita Sari; Ariawan Gunadi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The objective of this journal study is to examine and analyze the safeguards for Secured Creditors regarding the enforcement of property guarantees following a bankruptcy ruling against the debtor. This research employs a normative legal approach, utilizing legislation, a conceptual perspective, and case studies. The findings indicate that the position of Secured Creditors in case number 527 K/Pdt. Sus-Pailit/2020 emphasizes that the right to execute on property guarantees remains intact, even with a 90-day suspension period post-bankruptcy decision. This suspension does not eliminate the preferential status concerning debt repayment. During this time, the curator is prohibited from selling or taking control of the collateral without the Secured Creditor's consent. Specific regulations are needed to protect Secured Creditors, ensuring that the execution of their property guarantees under suspension remains under their oversight, to promote fairness, legal certainty, and proportional protection of their rights during the bankruptcy process.